A state‐of‐the‐art review on conventional, soft computing, and hybrid techniques for shading mitigation in photovoltaic applications. (13th April 2020) - Kumar, Nikhil; Nema, Savita; Nema, Rajesh K.; Verma, Deepak
Summary: This article intends to present a compendious review to extract maximum power in solar photovoltaic (PV) systems under varying environmental conditions and partial shading conditions by enumerating various circuit‐based topologies and different state‐of‐the‐art maximum power point techniques (MPPT). Partial shading reduces the overall efficiency of the PV system; therefore techniques that are dealing with partial shading play an important part in the power conditioning unit of all PV system connected to the stand‐alone mode or grid mode. Various circuit‐based topologies and various algorithms have been broadly discussed till date. As every algorithm is associated with its own merits and demerit, hence an extensive literature survey is required while planning for PV generating station under normal and partial shading condition. In this article, a comprehensive review of shading mitigation using different topologies has been done. The article on shading mitigation is broadly divided into two major groups. The first group includes all major circuit‐based topologies and the second group includes MPPT based techniques, which has been further classified into modified conventional techniques, soft computing techniques, and hybrid techniques. This comprehensive review presents an assessment of all techniques according to parameters like converter used, tracking speed, complexity, efficiency, number of sensors under partial shading condition would certainly provide a single platform to carry forward their research in solar PV application.